Allowances and Valuation Allowances – Essential Elements for the Presentation of the Fair View of the Financial Statements - Elena STĂNCIULESCU (CECCAR Business Review, 2020)

(untitled)
This article presents the accounting and fiscal treatment of allowances and valuation allowances. In order to achieve the accounting’s objective of providing the fair view, it is required that all accounting principles are followed and the allowances or impairment losses of assets are recorded, whether deductible or non-deductible, considering their significant role regarding the financial statements.